1997
DOI: 10.1128/aac.41.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance among clinical isolates of Haemophilus influenzae in the United States in 1994 and 1995 and detection of beta-lactamase-positive strains resistant to amoxicillin-clavulanate: results of a national multicenter surveillance study

Abstract: A total of 1,537 clinical isolates of Haemophilus influenzae were recovered in 30 U.S. medical center laboratories between 1 November 1994 and 30 April 1995 and were characterized in a central laboratory with respect to serotype and beta-lactamase production and the in vitro activities of 15 oral antimicrobial agents. Overall, 36.4% of the isolates were found to produce beta-lactamase. The rank order of activity of six cephalosporins on the basis of MICs was cefixime > cefpodoxime > cefuroxime > lorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
116
3
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(135 citation statements)
references
References 27 publications
14
116
3
2
Order By: Relevance
“…In recent reports of studies conducted in North America and Europe, the rates of b-lactamase production found in Moraxella catarrhalis isolates have exceeded 90%, with minor geographic variation [2,4,5,6,8,9]. Most of the Moraxella catarrhalis isolates in the present study were resistant to ampicillin, presumably due to b-lactamase production, as suggested by other reports, but the MIC90 scores remained low for amoxicillin/clavulanate, cefaclor, loracarbef, cefuroxime, azithromycin and ciprofloxacin ( Table 2).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In recent reports of studies conducted in North America and Europe, the rates of b-lactamase production found in Moraxella catarrhalis isolates have exceeded 90%, with minor geographic variation [2,4,5,6,8,9]. Most of the Moraxella catarrhalis isolates in the present study were resistant to ampicillin, presumably due to b-lactamase production, as suggested by other reports, but the MIC90 scores remained low for amoxicillin/clavulanate, cefaclor, loracarbef, cefuroxime, azithromycin and ciprofloxacin ( Table 2).…”
Section: Resultssupporting
confidence: 68%
“…BLNAR isolates are not only characterized by ampicillin resistance (MIC64 mg/ml), they are also distinguished by reduced susceptibility to amoxicillin/clavulanate and other b-lactam antibiotics [4]. In contrast, clinical isolates of Moraxella catarrhalis, as documented in recent North American and European studies, have reported rates of b-lactamase production of 1 90%, with minor geographic variation [2,4,5,8,9]. Presently, resistance to antibiotics other than ampicillin has not emerged as a concern with regard to Moraxella catarrhalis [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotypes or serogroup 19F, 23F, and United States. 19,20 BLNAR strains had been isolated at low frequencies in the 1980s, but BLNAR strains have rapidly increased at the rate of 19.5% in the 1990s. 22 Recently, the rate of BLNAR was 58.1% in Korea, 37% in Japan, 0%-33% in Europe, and 4%-10.1% in the USA.…”
mentioning
confidence: 98%
“…The prevalence of BLNAR increased up to 2.5%-10.1% in 1994-1995. 10 A recent study reported the BLNAR H. infl uenzae in European countries to range from 1.5% to 33.9%. 11 In Japan Hasegawa et al 12 reported 5.8% and 34.5% in BLNAR in 2000 and 2004, respectively.…”
mentioning
confidence: 99%